Biochemical Composition of the Teeth and the Effect of the Various Chemical Elements on their Structure - S. Dolinská; V. Tomečková (Czech Dental Chamber, 2017)
Introduction and objectives: The main objective of this review article is a detailed description of the tooth structure, bioorganic and bioinorganic composition of the tooth components, the protective biochemical process of tooth which can protect against tooth caries and processes which might damage the integrity of the tooth. The next section of this work describes the effect of various dietary chemical elements which are involved in the stronger teeth structure and increase the resistance of teeth against the effect of acids. Methods: Analysis of teeth composition, comparison of different chemical elements from diet. Results: Defense capability of enamel enhances suitable enamel structure and biochemical composition, especially the fact that each enamel crystal is covered with shell "rod sheath" that is more mineralized than the other layers of enamel. This structure contains iron and magnesium. The combination of these two elements gives the enamel a desired resistance to acids. Enamel proteins play an important role in the enamel. Proteins strengthen a enamel and regulate the development of hydroxyapatite crystals. For maintaining healthy teeth and mainly the enamel are needed several chemical elements (boron, silicon, calcium, magnesium, phosphorus), vitamins (D, K) and animal proteins, which enhances the absorption of calcium and magnesium. Noble metals (silver, gold, platinum) act as antiseptic and antioxidant elements. On the other hand, there are substances which damages the health of teeth, especially phytic acid, oxalic acid, citric acid, increased amount of saccharides and fats reduce the resorption of calcium. Lead displaces calcium from the tooth structure and lectins interfere with the absorption of nutrients needed for teeth. Conclusion: This work describes in detail the individual components of tooth and bioorganic and bioinorganic composition of tooth. Bioorganic part showed in highly mineralized tooth important role in maintaining the integrity of the tooth. The right combination of elements, vitamins from varied diet and sun exposure contribute to maintaining healthy teeth.